Psychoactive substance use, internet use and mental health changes during the COVID-19 lockdown in a French population: A study of gender effect - Malandain, Leo; Fountoulakis, Konstantinos N.; Syunyakov, Timur; Malashonkova, Evgeniia; Smirnova, Daria; Thibaut, Florence (Frontiers in Psychiatry, 2022)
Introduction: COVID-19 has enormous impacts on each individual. The goals of our study were (1) to assess the rate of internet and psychoactive substance use, clinical depression and anxiety in a French population during the lockdown (2) to study the role of clinical and socio-demographic variables (especially, gender). Material and methods: During lockdown, an online anonymous questionnaire was used to assess socio-demographic and health data, previous psychiatric history, anterior and current internet and psychoactive substance use, current anxiety, depression and suicidal ideation. The associations of socio-demographic, clinical variables with anxiety, depression, internet or psychoactive substance use were examined. Results: The study included 263 participants (aged 38.115.3 - 197 males and 64 females). During the lockdown, internet use increased in 14.4% of cases, alcohol use in 20.2%, and tobacco use in 6.8%. In contrast, more participants reported a decrease in alcohol, tobacco or illicit drug use (25.9, 24 and 27.8% respectively). Anxiety was reported in 62.4% and depression in 20.2% of cases; 29.7% of participants reported an increase in anxiety and 25.5% an increase in depression. Depression was associated with an increase in internet and tobacco use. Tobacco and alcohol use were positively associated and an increase in use was more frequent in previous users of both substances. Maintaining a daily routine and relationships with family, being self-employed were associated to lower risks of depression and anxiety. Conclusion: Higher rates of internet use, as well as depression and anxiety, were observed during the lockdown. Gender was not a significant associated factor.